POTENTIAL IMPLEMENTATION OF INCENTIVES AND DISINCENTIVES FOR HOUSEHOLD WASTE SOURCE SEPARATION IN BANDUNG CITY - Kezia Safitri, Elizabeth
The separation of household waste at the source in Bandung City is necessary to prevent another waste emergency, which happened previously in 2023 due to the Sarimukti landfill fire. One approach to encourage this is the implementation of incentives and disincentives. A study is needed to understand the current state of household waste source separation behaviors among the residents of Bandung, the factors influencing these behaviors, and the potential incentives and disincentives that could be implemented to promote better waste management practices. Primary data for this study were obtained through a questionnaire distribution to 187 respondents, consisting of both native and migrant residents of Bandung City. The analysis was conducted descriptively and statistically. The results showed that household waste separation behavior in Bandung is varied, but relatively low, with an average of 2,4 based on the likert scale (1-5) and deviation standard of 2,3. Factors related to waste separation behavior include age, number of family members, residency status, last educational level, monthly income, attitudes, knowledge, situational factors such as land availability, time, facilities, and a system for collecting separated waste, as well as trust in the surrounding community. Recommendations provided include a scheme for segregated waste collection, the implementation scheme for incentives and disincentives, and the amount of incentives and disincentives to be applied. Recommendations were selected using the Simple Additive Weighting (SAW) method. The recommended segregated waste collection system is a mix of door-to-door (DtD) and drop-off systems. Recommended incentives are waste handling fee reductions, awards/certificates, and the provision of waste processing facilities, while recommended disincentives include fines and restrictions on the provision of infrastructure and facilities. The recommended magnitude of incentives and disincentives chosen is 50% of the waste management fee, also considering the Willingness to Pay (WTP) and Ability to Pay (ATP) of Bandung citizens, which is Rp 23,403.74 (WTP) and Rp 31,990.03 (ATP). The amount of fines can be adjusted to ensure a deterrent effect on recipients of disincentives